Church and Society in Japan Today (The ecumenical review, 1956)
The following article is based on a report prepared by the Social Problems Committee of the National Christian Council of Japan and submitted to the World Council's Department on Church and Society as preparatory documentation for the new ecumenical study on “rapid social change.”